The effects of pH, surfactant, ion concentration, coformer, and molecular arrangement on the solubility behavior of myricetin cocrystals - Shuzhen Ren; Mingyu Liu; Chao Hong; Guowen Li; Jiabin Sun; Jianying Wang; Lei Zhang; Yan Xie (Elsevier, 2019)
Pharmaceutical cocrystals are a promising technology that can be used to improve the solubility of poor aqueous compounds. The objective of this study was to systematically investigate the solubility of myricetin (MYR) cocrystals, including their kinetic solubility, thermodynamic solubility, and intrinsic dissolution rate (IDR). The effects of pH, surfactant, ion concentration, and coformers on the cocrystal solubility were evaluated. Furthermore, single crystal structures of MYR, myricetin-isonicotinamide (MYR-INM) and myricetin-caffeine (MYR-CAF) cocrystals were analyzed to discuss the possible reasons for the enhancement of cocrystal solubility from the perspective of the spatial structure. The results indicated that the kinetic solubility of MYR cocrystals was modulated by pH and cocrystal coformer (CCF) ionization in buffer solution, while it primarily depended on the CCF solubility in pure water. In addition, the solubility of MYR cocrystals was increased in a concentration dependent fashion by the surfactant or ion concentration. The thermodynamic solubility of MYR-INM (1:3) cocrystals decreased with the increases of the pH value of the dissolution media. The IDR of MYR cocrystals was faster than that of MYR in the same medium and extremely fast in pH 4.5 buffer. The improved solubility of MYR cocrystals was probably related to the alternate arrangements of MYR and INM/CAF molecules and increased intermolecular distance. The present study provides some references to investigate the solubility behavior of pharmaceutical cocrystals. KEY WORDS: Cocrystal solubility, Myricetin, pH, Coformer, Crystal structure